1979
DOI: 10.1515/mamm.1979.43.4.543
|View full text |Cite
|
Sign up to set email alerts
|

Rendement d’assimilation et bilan énergétique chez les éléphanteaux d’Afrique (Loxodonta africana Blumenbach)

Abstract: Le but de cet article est d'etablir les rendements bioenergetiques et le bilan nutritionnel des jeunes 61£phants.Deux Elephanteaux apprivois£s äg£s de 27 et 31 mois, ont ete maintenus en enclos et nourris des meines plantes que eel les qu'ils choisissent en liberte. La quantity de nourriture qu'ils ont mangle a et^ mesuree avec precision ainsi que les reject a provenant de cette nourriture.Les rlsultats donnent des taux de digestibility des aliments naturels (assimilation/consommation) de 38,8 ± 4,4 % et de 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…The results of this study are generally in accord with corresponding literature data (Table 7). High intakes in that data set were achieved by growing animals (Monfort and Monfort, 1979;Spala et al, 1990), which compares well with the intake observed in elephant no. 1 from this study.…”
Section: Intake and Digestibility Datasupporting
confidence: 79%
See 1 more Smart Citation
“…The results of this study are generally in accord with corresponding literature data (Table 7). High intakes in that data set were achieved by growing animals (Monfort and Monfort, 1979;Spala et al, 1990), which compares well with the intake observed in elephant no. 1 from this study.…”
Section: Intake and Digestibility Datasupporting
confidence: 79%
“…Gross energy (GE) was determined by bomb calorimetry using an IKA ® ‐Calorimeter C 4000 adiabatic (Janke & Kunkel, Staufen, Germany). Chromium oxide was determined according to Petry and Rapp (1970). After wet ashing, calcium (Ca) was determined by flame photometry (Eppendorf ® Elex 6361, Eppendorf, Hamburg, Germany) and phosphorus (P) by measuring the increase in coloration of the ashed sample with ammonium molybdic acid and ammonium vanadic acid (1 : 1) by spectralphotometry.…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
“…From common hippos on roughage diets we know that DMI ranges from 22–45 g kg −0.75 day −1 which nicely matches the predicted limitation (Field 1970, Arman and Field 1973, Clauss et al 2004); in contrast, the reported or estimated food intake of elephants is between 98–157 g kg −0.75 day −1 for free‐ranging (Monfort and Monfort 1979, Meissner et al 1990, Ruggiero 1992) and 63–183 g kg −0.75 day −1 for captive elephants on forage‐only diets (Hackenberger 1987, Roehrs et al 1989, Clauss et al 2003). Free‐ranging elephants spend 75% of the day foraging (Hendrichs 1971, Wyatt and Eltringham 1974, Vancuylenberg 1977), in contrast to hippos which are known to spend only 30% of the day foraging (Verheyen 1954, Owen‐Smith 1988).…”
Section: Discussionsupporting
confidence: 62%
“…From common hippos on roughage diets we know that DMI ranges from 22Á45 g kg (0.75 day (1 which nicely matches the predicted limitation (Field 1970, Arman and Field 1973, Clauss et al 2004; in contrast, the reported or estimated food intake of elephants is between 98Á157 g kg (0.75 day (1 for free-ranging (Monfort and Monfort 1979, Meissner et al 1990, Ruggiero 1992) and 63 Á183 g kg (0.75 day (1 for captive elephants on forage-only diets (Hackenberger 1987, Roehrs et al 1989, Clauss et al 2003. Freeranging elephants spend 75% of the day foraging (Hendrichs 1971, Wyatt and Eltringham 1974, Vancuylenberg 1977, in contrast to hippos which are known to spend only 30% of the day foraging (Verheyen 1954, Owen-Smith 1988.…”
Section: Discussionsupporting
confidence: 53%